Can We Put Aside Microelectrode Recordings in Deep Brain Stimulation Surgery? - Pastor, Jesús (Brain Sci, 2020)
Microelectrode recording (MER) in deep brain stimulation (DBS) surgery has long been a recognized and efficient method for defining a target. However, in recent decades, imaging techniques, including DBS surgery, have experienced significant growth. There is convincing evidence that imaging-guided surgery can be helpful for targeting anatomically well-defined nuclei (e.g., subthalamic nucleus (STN) or internal globus pallidus (GPi)), and reductions in secondary effects have also been claimed. It has even been proposed that MER is not necessary to perform DBS, identifying in this way asleep surgery and imaging-guided DBS. However, there are several reasons why this is not the case. Neurophysiological techniques can efficiently and safely help to identify neural structures even in sleeping patients (e.g., different types of evoked potentials or motor stimulation). Deep nuclei are not homogeneous structures (even STN), so it is important to identify different places inside the putative target. Evidently, this is more relevant in the case of thalamic or hypothalamic surgery. Moreover, it is important to remember that the clinical and scientific knowledge acquired during DBS surgery can be important to gain further insight into pathologies and develop more effective treatments. Finally, the cost/efficiency of medical technology should be considered.